LAK21: 11th International Learning Analytics and Knowledge Conference 2021
DOI: 10.1145/3448139.3448143
|View full text |Cite
|
Sign up to set email alerts
|

Charting the Design and Analytics Agenda of Learnersourcing Systems

Abstract: Learnersourcing is emerging as a viable learner-centred and pedagogically justified approach for harnessing the creativity and evaluation power of learners as experts-in-training. Despite the increasing adoption of learnersourcing in higher education, understanding students' behaviour while engaged in learnersourcing and best practices for the design and development of learnersourcing systems are still largely under-researched. This paper offers data-driven reflections and lessons learned from the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Previous research has identified many potential benefits to co-creation of curriculum between students and academic staff, including reduced power disparities, deeper engagement, deep learning, increased motivation to study, better academic literacy, and more developed peer communities (Bergmark & Westman, 2016;Cook-Sather, 2014;Deeley & Bovill, 2017;Khosravi et al, 2021;Rust et al, 2003;Shibani et al, 2020). In this study, we investigated the interaction between types of student engagement with a platform for co-creation of learning resources, and student satisfaction and academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified many potential benefits to co-creation of curriculum between students and academic staff, including reduced power disparities, deeper engagement, deep learning, increased motivation to study, better academic literacy, and more developed peer communities (Bergmark & Westman, 2016;Cook-Sather, 2014;Deeley & Bovill, 2017;Khosravi et al, 2021;Rust et al, 2003;Shibani et al, 2020). In this study, we investigated the interaction between types of student engagement with a platform for co-creation of learning resources, and student satisfaction and academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…RiPPLE [85] is an AES that takes the crowdsourcing approach of partnering with students, also referred to as learnersourcing [84], to create the resource repository. Figure 2 uses screenshots of the platform to demonstrate some of its main functionality.…”
Section: Adaptive Educational Systemsmentioning
confidence: 99%
“…Below we outline our key learnings and insights from our experience, which spans development and adoption of RiPPLE in over 100 courses across a range of disciplines including Medicine, Pharmacy, Psychology, Education, Business, Computer Science, and Biosciences with roughly 25,000 students who have authored over 50,000 learning resources and over 2 million interactions on these resources. A more in-depth analysis of the case study is available in [84].…”
Section: Adaptive Educational Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3(b) presents the RiPPLE interface for creating a multi-answer question. Not only does this reduce the cost of content generation, but it also holds the potential to foster students' higher-order skills, such as evaluative judgment (Doroudi et al, 2018;Khosravi, Demartini, Sadiq, & Gasevic, 2021). However, since students are still developing their expertise, and even though they are encouraged to reflect on the quality of their work, it is likely that some learning resources created will be ineffective, inappropriate, or incorrect (Bates, Galloway, Riise, & Homer, 2014).…”
Section: System Purposementioning
confidence: 99%